Atomic Imaging of Electrically Switchable Striped Domains in β′‐In2Se3. Issue 17 (2nd July 2021) - Chen, Zhi; Fu, Wei; Wang, Lin; Yu, Wei; Li, Haohan; Tan, Clement Kok Yong; Abdelwahab, Ibrahim; Shao, Yan; Su, Chenliang; Sun, Mingzi; Huang, Bolong; Loh, Kian Ping
Abstract: 2D ferroelectricity in van‐der‐Waals‐stacked materials such as indium selenide (In2 Se3 ) has attracted interests because the ferroelectricity is robust even in ultrathin layers, which is useful for the miniaturization of ferroelectric field effect transistors. To implement In2 Se3 in nanoscale ferroelectric devices, an understanding of the domain structure and switching dynamics in the 2D limit is essential. In this study, a biased scanning tunnelling microscopy (STM) tip is used to locally switch polarized domains in β ′‐In2 Se3, and the reconfiguration of these domains are directly visualized using STM. The room‐temperature surface of β ′‐In2 Se3 breaks into 1D nanostriped domains, which changes into a zig‐zag striped domains of β ″ phase at low temperatures. These two types of domains can coexist, and by applying a tip‐sample bias, they can be interchangeably switched locally, showing volatile or nonvolatile like behavior depending on the threshold voltage applied. An atomic model is proposed to explain the switching mechanism based on tip‐induced flexoelectric effect and the ferroelastic switching between β ′ and β ″ phases. Abstract : With applying tip‐sample bias, field‐driven reversible switching of polarization patterns between antiferroelectric β ′ and ferroelectric β ″ phases In2 Se3 are directly visualized in atomic resolution using scanning tunnelling microscopy.